Post-2015: how to design goals for (inter)national action? - Heiner Janus; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
United Nations (UN) Member States agreed to start negotiations towards a universal sustainable development agenda. A major challenge is to design goals that guide future action at the national and international levels. These “Goals” usually refer to global development priorities at the highest aggregated level. “Targets” are subcomponents of goals that are needed to achieve the overarching goal. “Indicators” help to monitor progress towards the targets. At the national level, countries prefer to set their own targets and indicators based on their own circumstances and needs. At the international level, setting global minimum standards for all citizens, or agreeing on global environmental ceilings, can ensure better development outcomes for all countries. International development goals can foster coherence in aggregating national actions in addressing global challenges. They can create accountability across countries and ensure comparability on development progress. Combining national development targets and international development goals within one unified agenda, however, is challenging in at least two ways. First, a balance has to be found between flexibility at the local level and a strong basis for accountability at the global level. National level target-setting takes account of local development conditions and allows room for flexibility in addressing complex development challenges. Goal-setting at the global level will, however, prescribe goals to be met by all countries, which may be more or less consistent with the targets set at the national level. Second, it is difficult to define ambitious goals that are meaningful in a heterogeneous world. Countries differ regarding income, poverty, equality and geography, for instance. Global standards and rules need to be ambitious, yet they have to be fair towards all countries. Designing a universal development agenda has to address the differentiation of countries and integrate national- and international-level development goals within one agenda. This paper examines three approaches for designing the post-2015 agenda: 1) the Millennium Development Goals approach (top-down negotiation), 2) the inductive approach (bottom-up) and 3) the two-tier-list approach (a hybrid of the two). Each approach is characterised by different advantages and disadvantages that decision-makers negotiating the post-2015 agenda need to consider carefully. This paper proposes five key questions for judging the merits of each approach: How are global and national development goals linked? How does the approach influence negotiations? Are sectorspecific and cross-cutting goals included? How does the approach foster accountability? How communicable will the future agenda be? In light of these considerations, the two-tier-list approach would allow for combining a list of global goals to foster global collective action with nationally set targets and indicators. The two-tier-list approach offers the greatest potential for designing an ambitious, communicable, accountable and relevant future development agenda.
Keywords: 330